From UV-bright Galaxies to Early Disks: The Importance of Turbulent Star Formation in the Early Universe - Vadim A. Semenov; Charlie Conroy; Lars Hernquist (The Astrophysical Journal)
Bursty star formation at early times can explain the surprising abundance of early UV-bright galaxies revealed by JWST but can also be a reason for the delayed formation of galactic disks in high-resolution cosmological simulations. We investigate this interplay in a cosmological simulation of an early-forming Milky Way analog with detailed modeling of the cold turbulent interstellar medium (ISM), star formation, and feedback. We find that the modeling of locally variable star formation efficiency (SFE) coupled with the ISM turbulence on the scales of star-forming regions is important for producing both early bursty evolution and early formation and survival of galactic disks. Such a model introduces a qualitatively new channel of the global star formation rate (SFR) burstiness caused by chaotic fluctuations in the average SFE due to changes in the ISM turbulence, which, in our simulation, dominates the short-term SFR variability. The average SFE stays low, close to ∼1% per freefall time, and its variation decreases when the gas disk forms, leading to only mild effects of stellar feedback on the early disk, enabling its survival. By rerunning our simulation with fixed SFE values, we explicitly show that low SFEs lead to smoother SFR histories and disk survival, while high SFEs lead to bursty SFRs and hinder disk formation. The model with variable SFE switches between these two regimes at the moment of disk formation. These trends are missing in more commonly used star formation prescriptions with fixed SFE; in particular, the prescriptions tying star formation to molecular gas should be interpreted with caution because the two are decoupled at early times, as we also show in this paper.